The integration of pop-culture into social media marketing campaign - Studying firm-generated memes in Hong Kong - LAI, Wing-Lam (2022)
With the prevailing use of internet memes (IM) as a social media marketing (SMM) tool, firms started creating their own memes, and integrating pop culture into their product promotion in the IM (Hecker, 2020). While there are only scant research focusing on IM and brand equity, and lacking research on how to manage the IM’s influence on brand, this study shifts the current paradigm of user-generated memes to firm-generated memes for a further study.